Evaluation of effectiveness of the using a pillow in children for dental rehabilitation under general anesthesia in term for facilitate intubation - Canpolat, Dilek Günay (Pak J Med Sci, 2016)
BACKGROUND AND OBJECTIVE: Airway safety may be provided with endotracheal intubation especially for oral procedures because of some potential risks such as aspiration of secretion or foreign bodies. In this study, we aimed to determine whether placing a pillow under the occiput may facilitate endotracheal intubation in non-cooperative children whose extensive dental treatments were planned to take place under general anesthesia. METHODS: The study was performed in Erciyes University, Faculty of Dentistry between March-July 2014. A total 150 ASA I-II children, between 3-9 years were included in this study. Pillow was folded under the occiput in Group 1 (n=75), patients lay on a flat surface in Group 2 (n=75) during the anesthesia induction and intubation period. RESULTS: There were no statistically significant differences between groups regarding the demographic data (age, weight, gender) (p>0.05). Operation times were similar in both groups (p=0.329). The number of intubation attempts was smilar in both groups (p=0.412). The intubation time was longer in group one than in group two (p= 0.025). CONCLUSION: We concluded that, placing a pillow under the patients occiput provided longer intubation time without changing the number of attempts in the normal airway in non-cooperative children whose extensive dental treatments were planned to take place under general anesthesia.